Clinical and epidemiologic characteristics associated with dengue fever in Mombasa, Kenya. (November 2020) - Lim, Jacqueline Kyungah; Matendechero, Sultani Hadley; Alexander, Neal; Lee, Jung-Seok; Lee, Kang Sung; Namkung, Suk; Andia, Esther; Oyembo, Noah; Lim, Sl-Ki; Kanyi, Henry; Bae, So Hee; Yang, Jae Seung; et al.
Highlights: Data are lacking on dengue in Africa. This surveillance covered the beginning of a dengue outbreak in April-May 2017. 61% of 482 patients with non-malarial fever in Mombasa were dengue-positive. Dengue cases presented with rash, retro-orbital pain, myalgia, arthralgia, etc. Dengue cases were mostly mild with only two cases requiring observation, and no DHF. Abstract: Objectives: Information on dengue in Africa is limited. To estimate the proportion of dengue-positive cases among febrile patients and describe clinical indicators of dengue, we conducted passive health facility-based fever surveillance in Mombasa, Kenya. Methods: Non-malarial febrile patients between one and 55 years were enrolled at three health facilities between March 2016 and May 2017. Acute and convalescent blood samples were collected with an interval of 10–21 days. Acute samples were tested with dengue RDT and a selected subset with RT-PCR, and acute/convalescent samples with IgM/IgG ELISA. Results: Among 482 enrollees, 295 (61.2%) were dengue-positive based on laboratory results. The surveillance covered the beginning of a dengue outbreak in April-May 2017, during which 73.9% of enrollees were dengue-positive. By contrast, during the non-outbreak period, 54.6% were dengue-positive. Dengue case status was positively associated with rash, fatigue, headache, retro-orbital pain, nausea/vomiting, nose bleeding, gum bleeding, loss of appetite, myalgia, and arthralgia. Dengue-positive cases in our study had mostly mild disease, with only two requiring observation, and no DHF. Conclusions: The clinical response was generally mild relative to what was observed in SE Asia and the Americas. Given the high level of DENV transmission in Mombasa, more data would be needed to further understand the disease burden and improve case detection for surveillance/monitoring of outbreaks.